Factors associated with death among postpartum women with COVID-19: a Brazilian population-based study - Anelise de Toledo Bonatti; Nathassia Miller; Maria Antonieta de Barros Leite Carvalhaes; Rodrigo Jensen; Cristina Maria Garcia de Lima Parada
Objective: to identify the factors associated with death due to COVID-19 among Brazilian postpartum women in the first five months of the pandemic and five subsequent months, and describe the sociodemographic and clinical characteristics of postpartum women who developed the disease. Method: cross-sectional population-based study using a secondary database available in the Sistema de Informação de Vigilância Epidemiológica da Gripe -SIVEP-Gripe (Influenza Epidemiological Surveillance Information System), Brazilian Ministry of Health. A total of 869 postpartum women were included, and the analysis considered the first five months of the pandemic and subsequent five months. Association between the variables of interest and outcome (death due to COVID-19/cure) was investigated using logistic regression. Results: most participants were aged between 20 and 34, of mixed race or Caucasian, and lived in the urban/peri-urban area. The proportion of deaths was 20.2% in the first period and 11.2% in the second. The likelihood of death increased in both periods due to the presence of respiratory signs and symptoms: dyspnea, respiratory distress, and oxygen saturation below 95%, in addition to the need for ventilatory support and intensive care. Conclusion: the proportion of deaths among postpartum women was high and decreased in the second period under study. Respiratory signs and symptoms, mechanical ventilation, and intensive care were associated with death in both periods.